Fulfillment Of The Rights Of Children In Conflict With The Law With The Law In The Child Development Institution Special Child Development Institution (Lpka) Class I Medan - Josep Manahan; Robi Krisna2 (LAWYER: Jurnal Hukum, 2023)
Children are the next generation of a nation, so that the growth and development of children must be considered properly, and even not only the responsibility of the family and parents but also the responsibility of society and the state, considering that Indonesia is a welfare state that has an obligation to guarantee the rights of its state colors properly. In this case, including the rights possessed by children in conflict with the law (ABH), even though they are children in trouble with the law, they are children who must be protected for the fulfillment of their rights. This study was conducted using the method of literature and document studies, in the form of books, journal articles, or other types of writings and various laws and regulations relating to cases of children in conflict with the law (ABH). The results of the study indicate that the fulfillment of the rights of correctional students consisting of the right to survive and develop, the right to protection and the right to participate has been carried out well by LPKA. Although there is still a lack of correction social workers in LPKA who act as facilitators and bridges for ABH to get education and carry out the rehabilitation process according to the needs of children.